Central Bank Swap Lines: Evidence on the Effects of the Lender of Last Resort. (8th November 2021) - Bahaj, Saleem; Reis, Ricardo
Abstract: Theory predicts that central-bank lending programs put ceilings on private domestic lending rates, reduce ex post financing risk, and encourage ex ante investment. This article shows that with global banks and integrated financial markets, but domestic central banks, then lending of last resort can be achieved using swap lines. Through them, a source central bank provides source-currency credit to recipient-country banks using the recipient central bank as the monitor and as the bearer of the credit risk. In theory, the swap lines should put a ceiling on deviations from covered interest parity, lower average ex post bank borrowing costs, and increase ex ante inflows from recipient-country banks into privately issued assets denominated in the source-country's currency. Empirically, these three predictions are tested using variation in the terms of the swap line over time, variation in the central banks that have access to the swap line, variation in the days of the week in which the swap line is open, variation in the exposure of different securities to foreign investment, and variation in banks' exposure to dollar funding risk. The evidence suggests that the international lender of last resort is very effective.